Eksplorasi Produk Interior Dari Material Plastik Daur Ulang dan Sisa Serbuk Kayu - Dewi, Meilisa; Wibowo, Mariana (Intra, 2019)
Nowadays, the existence of plastic waste on earth has become a threat to the environment, including Indonesia. The rapid growth of the amount of plastic waste makes it an even more urgent problem to be solved. However, Indonesia’s waste management and processing system are yet to be proven as effective. The utilization of plastic waste in the creative industry is also very low, especially in the interior sector. As an interior designer, this is the gap to create innovations in the interior sector, by using many kinds of recycled plastic materials for the interior product. This design process will use the design thinking method created by D. School, which consist of a few processes such as empathize, define, ideate, prototype, test, and implement. The products produced are a coffee table, stool, chair, table lamp and wall art as introduction products to educate people that products made from recycled materials can become a wide variety of interior products. The end results of this thesis are three series of furniture, and all three used different characteristics of recycled plastic materials, which are composite plastic with sawdust, opaque plastic combined with transparent plastic, and full opaque plastic. These plastics became a variation on the interior products that are made from wood and iron. With contrast color palettes and diverse technique, the plastic variation can become the products’ focal-point, so the character of the plastic can be optimized.